Transabdominal ultrasonographic findings in children with sickle cell anemia in Sokoto, North-Western Nigeria - Ma’aji, Sadisu; Baba, Mohammed; Gele, Haruna; Musa, Abubakar; Jibril, Baba; Sani, Usman; Yunusa, Garba; Danfulani, Muhammad; Saidu, Sule; Jiya, Muhammed; Bello, Samaila (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Sickle cell anemia (SCA) is an inherited disease caused by production of abnormal hemoglobin chains within the red blood cell. In Nigeria, West Africa, the incidence of SCA is 3%. The most common abdominal manifestations include abdominal pain (mesenteric crisis), hepatomegaly, splenomegaly, autosplenomegaly, and cholelithiasis. Objective: To evaluate the abnormal transabdominal ultrasonographic (TAUS) findings in children with sickle cell anemia in Sokoto, Northwestern Nigeria. Materials and Methods: Pediatric patients with SCA attending the sickle cell clinic at the Department of Pediatrics, Usmanu Danfodiyo University Teaching Hospital Sokoto were scanned at the Radiology Department of the Hospital by transabdominal ultrasonography (TAUS) using Apogee 800 plus Ultrasound scanner with a variable frequency probes at 5-12 MHz. The patients were in their steady states. They were also screened for viral hepatitis B and C. Results: The commonest TAUS findings in this study was hepatomegaly in 70 (98.6%) patients followed by splenomegaly in 15 (21.1%), autosplenomegaly in 3 (4.2%), and gallbladder sludge in 2 (2.8%) patients. Conclusion: Transabdominal ultrasonographic imaging of patients with sickle cell anemia revealed a high prevalence of abdominal abnormalities, especially of the liver, spleen, and gallbladder.